Ultra-Processed Foods and Sarcopenia-Related Conditions among Older Adults: A Systematic Review - Sari, Eka Puspita; Dewi, Citra Kumala; Harianja, Ristina Rosauli; Mollet, Genoveva C (RRZ Scientific Publishing, 2026)
The increasing elderly population has contributed to the growing prevalence of sarcopenia-related conditions among older adults. Nutritional factors, including the consumption of ultra-processed food (UPF), are suspected to play a role in the decline of muscle health, frailty, and physical function in the elderly. This systematic review aimed to evaluate the association between ultra-processed food consumption and sarcopenia-related conditions among older adults. This study employed a systematic review method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted through the PubMed and ScienceDirect databases in May 2026. Observational studies assessing the association between UPF consumption and sarcopenia-related outcomes were included in this review. A total of 11 studies were included in this systematic review. Most studies demonstrated that high UPF consumption was associated with an increased risk of frailty, reduced muscle strength, low physical performance, increased body fat, lower skeletal muscle mass, and a higher risk of sarcopenic obesity among older adults. However, several studies did not report statistically significant associations. High consumption of ultra-processed food tends to be associated with various sarcopenia-related conditions in older adults. Limiting UPF intake and adopting healthy dietary patterns may help maintain muscle health and physical function in the aging population.